Analisis Pemberdayaan Pemuda di Kota Makassar - M. Adhistiran (Departemen Ilmu Pemerintahan Fisip Unhas, 2026)
Youth are strategic assets in regional development, playing important roles as agents of change, drivers of development, and productive human resources within society. However, high unemployment rates, limited access to education, low participation in decision-making processes, and suboptimal creativity development remain major challenges faced by young people in Makassar City. Therefore, the local government, through the Youth and Sports Office (Dispora), has implemented various empowerment programs aimed at improving the capacity, competence, and competitiveness of youth. This study aims to analyze the role of the Makassar City Government in youth empowerment. The research employed a qualitative descriptive approach. Data were collected through interviews, observations, documentation, and literature review. The informants consisted of government officials, youth organizations, and community leaders involved in youth empowerment programs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that youth empowerment in Makassar City is implemented through education and training programs, the Study While Working Scholarship Program, and youth creativity development programs. These initiatives have contributed to improving skills, educational opportunities, work experience, innovation, and youth creativity. Nevertheless, several challenges remain, including inadequate program dissemination, limited accessibility for some youth groups, and the need to strengthen collaboration with the private sector and youth organizations. Therefore, more integrated efforts are required to enhance the effectiveness of youth empowerment programs in Makassar City.